Upaya Mengembangkan Kewirausahaan Siswa Dengan Pemanfaatan Limbah Sampah Anorganik Dan Organik Menjadi Barang Bernilai - Slamet Mudjijanto (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2025)
Waste management is a critical issue in maintaining environmental sustainability, especially in school settings where the character of the younger generation is shaped. This study aims to explore the implementation of inorganic and organic waste management methods through a Waste Bank program and compost production at UPT SD Negeri 75 Gresik. This program has been running for approximately two years and has shown positive impacts by creating a cleaner and healthier school environment, saving costs through the use of organic waste as compost, and opening entrepreneurial opportunities for students through the sale of recycled products. The results indicate that the success of this program is supported by several factors, including a green school environment, strong support from the school community and stakeholders, and waste management skills possessed by most of the school community. However, the program also faces several challenges, such as limited facilities and infrastructure, lack of meticulousness in waste processing, and limited time and funding for entrepreneurship support. To overcome these challenges, collaboration between the school, committee, and surrounding community is needed, as well as enhanced skills training and entrepreneurship development among teachers and students. With sustained efforts and support from various parties, UPT SD Negeri 75 Gresik can serve as a model for effective and sustainable waste management in school environments. This study is expected to contribute to the development of better waste management strategies and serve as a reference for other schools in implementing similar programs.